Changes in the Use of Lumbar Arthrodesis Procedures Within Accountable Care Organizations. Issue 7 (1st April 2019) - Schoenfeld, Andrew J.; Sturgeon, Daniel J.; Harris, Mitchel B.; Blucher, Justin A.; Kang, James D.; Haider, Adil H.; Bono, Christopher M.
Abstract : Study Design: A retrospective review of Medicare claims data (2009–2014). Objective: The aim of this study was to evaluate changes in the use of lumbar fusion procedures following the formation of Accountable Care Organizations (ACOs). Summary of Background Data: Within surgical care afforded by ACOs, savings are thought to be realized by improved care coordination as well as reductions in the use of preference-sensitive procedures such as lumbar fusion. Methods: We queried fee-for-service claims for patients enrolled in Medicare Part A and B, identifying patients who received lumbar spine fusion, discectomy, or decompression procedures. We performed a difference-in-differences analysis comparing the use of lumbar fusion in ACOs and non-ACOs in the period before (2009–2011) and after (2012–2014) ACO formation. Propensity score adjustment was used to address differences in case-mix. Multivariable logistic regression was used to compare the likelihood of receiving a lumbar fusion in ACOs and non-ACOs in the period before and after ACO formation. Results: Within organizations that would form ACOs, the raw rate of lumbar fusion increased from 50% (n = 2183) in 2009 to 2011 to 54% (n = 2283) in 2012 to 2014. Among non-ACOs, the use of fusion increased from 52% (n = 110, 160) to 59% (n = 109, 917). Adjusted difference in differences in the use of lumbar fusion between ACOs and non-ACOs was -2.6 percentage points ( P = 0.13). When limited to patients with spinal stenosis, ACOs significantly reduced the use of fusion (-5.8 percentage points; P = 0.03). Conclusion: Our results indicate that ACOs may effectively curtail the use of lumbar fusion procedures, particularly among patients with spinal stenosis. As these interventions are often associated with higher complications and need for reoperation, such practices might accrue additional health care savings for Medicare beyond those realized during the index surgical period. Level of Evidence: 3 Abstract : In this review of Medicare claims (2009-2014) data to assess the influence of Accountable Care Organizations (ACOs) on the use of lumbar fusion, ACOs significantly reduced the use of fusion among patients with spinal stenosis. Overall, there was no significant difference in the use of fusion between ACOs and non-ACOs.